Correction of Alcoholic Postcomatose Disorders by Intravenous Laser Blood Irradiation: A Clinicoexperimental Study - L. T. Idrisova; D. A. Yenikeyev; G. A. Baiburina (Общая реаниматология)
The authors studied the impact of intravenous laser hemotherapy on the course of rat alcoholic coma caused by intragastric 40% ethanol administration. Intravenous laser blood irradiation promoted reduced mortality rates, diminished neurological deficit, earlier clinical recovery, and the optimized sympathetic/parasympathetic central nervous system ratio. Clinical and functional studies of changes in the central nervous system and retina were made in patients admitted for alcoholic coma. Intravenous laser blood irradiation as part of complex detoxification therapy positively affected the altered function of the higher nervous activity, contributed to earlier conscious recovery and emergence from coma, diminished neurological deficit in the early postcomatose period — alleviated brain edema, a drastic relief of pyramidal insufficiency and cramps, which was detectable in the visual assessment of electroencephalograms, their spectral coherent analysis, as well in the analysis of systemic and regional electroretinography.